Hacktivism 1-2-3: how privacy enhancing technologies change the face of anonymous hacktivism - Balázs Bodó (Internet Policy Review)
This short essay explores how the notion of hacktivism changes due to easily accessible, military grade Privacy Enhancing Technologies (PETs). Privacy Enhancing Technologies, technological tools which provide anonymous communications and protect users from online surveillance enable new forms of online political activism. Through the short summary of the ad-hoc vigilante group Anonymous, this article describes hacktivism 1.0 as electronic civil disobedience conducted by outsiders. Through the analysis of Wikileaks, the anonymous whistleblowing website, it describes how strong PETs enable the development of hacktivism 2.0, where the source of threat is shifted from outsiders to insiders. Insiders have access to documents with which power can be exposed, and who, by using PETs, can anonymously engage in political action. We also describe the emergence of a third generation of hacktivists who use PETs to disengage and create their own autonomous spaces rather than to engage with power through anonymous whistleblowing.